(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article is devoted to the spiritual and moral education of students, the development of methods and forms, the assimilation of their content in the minds of students, at the same time awakening the love of the Motherland among young people, learning to appreciate work, the formation of spiritual and cultural relations with peers, the development of spiritual and moral competencies.